2022
DOI: 10.1186/s12884-022-04956-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric properties of the maternal ambivalence scale in spanish women

Abstract: Background maternal ambivalence, which refers to experiencing mixed emotions about motherhood, like happiness and sadness, is frequent during the perinatal period. Aim Due to the relevance of this topic and the lack of psychometrically-sound instruments to measure it, this study aims to develop and test a measure of maternal ambivalence called the Maternal Ambivalence Scale (MAS). Methods in this cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Other biopsychosocial variables associated with increased likelihood of experiencing perinatal depression are health problems in the baby, a non-vaginal or instrumented delivery (Dekel et al, 2019), lack of social support (Racine et al, 2020), marital dissatisfaction (Whisman et al, 2011, low socioeconomic and educational status, ethnic minority background, high psychological, and biological stress (Glover et al, 2010;Lobel et al, 2022), high neuroticism (Martín- Santos et al, 2012), tendency to excessive rumination and worry (Osborne et al, 2021;Petrošanec et al, 2022), high perfectionism (Maia et al, 2012), anxious/insecure attachment styles and passive coping (Gutiérrez-Zotes et al, 2015;Warfa et al, 2014), such as a tendency to self-blame and distractibility and difficulty reframing problems in a positive way (Gutiérrez-Zotes et al, 2016), low self-and partner motivation to have a baby (Reut & Kanat-Maymon, 2018), the existence of a substance abuse disorder (Chapman & Wu, 2013), family history of depressive or anxiety disorders, or the experience of multiple, unwanted, particularly difficult or adolescent childbirth (Hutchens & Kearney, 2020;Meuti et al, 2015;Puyané et al, 2022;Soto-Balbuena et al, 2018;Van Niel & Payne, 2020). In the case of adolescent females, in addition, family criticism, self-esteem, and perceived self-efficacy seem to become particularly important (Recto & Champion, 2017).…”
Section: Risk Factors and Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Other biopsychosocial variables associated with increased likelihood of experiencing perinatal depression are health problems in the baby, a non-vaginal or instrumented delivery (Dekel et al, 2019), lack of social support (Racine et al, 2020), marital dissatisfaction (Whisman et al, 2011, low socioeconomic and educational status, ethnic minority background, high psychological, and biological stress (Glover et al, 2010;Lobel et al, 2022), high neuroticism (Martín- Santos et al, 2012), tendency to excessive rumination and worry (Osborne et al, 2021;Petrošanec et al, 2022), high perfectionism (Maia et al, 2012), anxious/insecure attachment styles and passive coping (Gutiérrez-Zotes et al, 2015;Warfa et al, 2014), such as a tendency to self-blame and distractibility and difficulty reframing problems in a positive way (Gutiérrez-Zotes et al, 2016), low self-and partner motivation to have a baby (Reut & Kanat-Maymon, 2018), the existence of a substance abuse disorder (Chapman & Wu, 2013), family history of depressive or anxiety disorders, or the experience of multiple, unwanted, particularly difficult or adolescent childbirth (Hutchens & Kearney, 2020;Meuti et al, 2015;Puyané et al, 2022;Soto-Balbuena et al, 2018;Van Niel & Payne, 2020). In the case of adolescent females, in addition, family criticism, self-esteem, and perceived self-efficacy seem to become particularly important (Recto & Champion, 2017).…”
Section: Risk Factors and Comorbiditymentioning
confidence: 99%
“…Another variable is ambivalence towards motherhood, understood as the coexistence of positive and negative feelings associated with being a mother (Martín-Sánchez et al, 2022), which has been traditionally silenced in this field and has been shown to play an important role in predicting a worsening of symptoms throughout the perinatal stage (Santos et al, 2017).…”
Section: Risk Factors and Comorbiditymentioning
confidence: 99%
“…Currently, there are no empirically validated instruments for assessing manageable–unmanageable maternal ambivalence. In previous research, maternal ambivalence has been primarily evaluated using qualitative interviews (Chapman & Gubi, 2019; Raneberg & MacCallum, 2023; Tuval-Mashiach & Shaiovitz-Gourman, 2014), with the exception of one study that used a quantitative measure, the Maternal Ambivalence Scale (MAS; Martín-Sánchez et al, 2022). However, the authors of the MAS conceptualized maternal ambivalence as doubts and convictions about wanting to be a mother and the coping strategies used to deal with ambivalence (i.e., expression/suppression).…”
mentioning
confidence: 99%